THE INFLUENCE OF READING HABIT ON STUDENTS’ WRITING SKILL - Endar Rachmawaty Linuwih; Yohanes Kurniawan Winardi (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2020)
This research aims to investigate the reading habit quality of EFL learners at Widya Kartika University, Surabaya and to find out the influence of reading habit towards students’ writing skill. This is a quantitative ex-post facto study since it examines how the independent variable (reading habit) that has existed affects the dependent variable (writing skill) and the result is in the form of numbers. Sixty two students of Widya Kartika University were selected as the subject of this study. The instruments used in this study were (1) a reading habit questionnaire, to measure the quality of students’ reading habit and (2) a writing test, to examine the students’ writing skill and how it is influenced by reading habit. The results showed that the students’ reading habit quality was fair. Meanwhile, the analysis of Simple Linear Regression concluded that reading habit influences students’ writing skill.  Moreover, one of the writing components that was mostly influenced by the reading habit was the content.